O Trabalho no campo do figurino no audiovisual brasileiro: reflexões sobre o passado, o presente e possíveis caminhos futuros para o ingresso na profissão - Dias Filho, Márcio Masselli (2024)
This qualitative research focuses on the work of costume design in Brazilian audiovisual, investigating the paths of education, entry into the profession, work dynamics, challenges, and professional recognition in the sector. Initially, through a bibliographic review, a brief overview of the national audiovisual industry is provided, followed by an overview of the costume departments’ technical sheets from film productions over the years, as well as a presentation of the work dynamics and roles within the costume department. Based on this, examples of various forms of costume education (formal, non-formal, and informal) in the country are presented as a possibility for preparation and entry into the profession, with the hypothesis that it is a process that promotes improvements in work and professional recognition in the field. Finally, the analysis of interviews with four professionals from the costume design field, coming from different backgrounds and training, enriches the analysis of entry into and the profession of the costume designer, broadening the understanding of the sector and its complexities. As a result, it is observed that the entry into the profession can occur in a multidimensional way. Unlike other more regulated professions, there is no single path or standard model of education for costume designers. It is also noted that the field of costume design can improve aspects of formal training by combining theory and practice applied to the different contexts in which costume designers can work, especially in audiovisual. Finally, the strengthening of the profession depends on greater structuring of professional education, recognition in the market, and greater appreciation of the technical and creative work of costume designers.